1991
DOI: 10.1128/aac.35.11.2371
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of cefepime and ceftazidime for treatment of skin, surgical wound, and complicated urinary tract infections in hospitalized subjects

Abstract: We undertook a prospective, randomized open comparison of the broad-spectrum cephalosporins cefepime and ceftazidime in treatment of hospitalized subjects with skin or wound infections and complicated nosocomial urinary tract infections. Cefepime treatment (dosage, 2.0 g intravenously twice daily for 4 to 28 days) was successful in 36 (90%) of 40 infections of the skin and skin structure or wounds and in 16 (84%) of 19 nosocomial urinary tract infections. Ceftazidime treatment, 2.0 g every 8 h, was successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Cefepime eradicated 97% of all pathogens, similar to comparator therapy (94%). Accordingly, this study extends the findings of previously published clinical studies, which found cefepime to be effective for the treatment of moderate to serious infections of the lower respiratory tract [19][20][21][22][23] and the urinary tract [24], as well as intraabdominal infections [25] and bacteremia [26].…”
Section: Discussionsupporting
confidence: 75%
“…Cefepime eradicated 97% of all pathogens, similar to comparator therapy (94%). Accordingly, this study extends the findings of previously published clinical studies, which found cefepime to be effective for the treatment of moderate to serious infections of the lower respiratory tract [19][20][21][22][23] and the urinary tract [24], as well as intraabdominal infections [25] and bacteremia [26].…”
Section: Discussionsupporting
confidence: 75%
“…Results comparable to those obtained with ceftazidime are observed with the use of cefepime in complicated UTI [92,104]. A total of 300 episodes of pyelonephritis were observed in pediatric patients enrolled in a randomized, open label, multicenter trial where cefepime was compared with ceftazidime (both administered parenterally at 50 mg/kg every 8 h).…”
Section: Clinical Efficacymentioning
confidence: 86%
“…However, several reviews have suggested that prolonged antibiotic exposures will achieve better PD profile [7,49,50]. Apparent benefits with regards to maximum bacterial killing also were reported in several studies when antibiotic concentrations were maintained above the MIC for extended periods, ideally four to five times the MIC especially when less susceptible microorganisms were involved [33,44,51-55]. In combination with other PK/PD data, it is suggested that therapeutic targets for CI therapy should be a steady-state concentration (C ss ) that is at least 4 x MIC [33].…”
Section: Reviewmentioning
confidence: 99%